METHODOLOGY OF USING VISUAL TOOLS IN TEACHING GEOMETRY TOPICS (Global Conference on Medical and Health Sciences, 2026)
Amid declining international mathematics scores, this paper proposes a methodological framework for integrating visual tools into geometry education to enhance student comprehension and engagement. Geometry, with its inherently visual nature, provides a fertile ground for leveraging technology to foster critical cognitive skills. This extended abstract outlines a structured approach that utilizes a range of visual aids, from Dynamic Geometry Software (DGS) like GeoGebra to immersive technologies such as Augmented and Virtual Reality (AR/VR). The methodology is grounded in established pedagogical models, including TPACK and SAMR, to ensure a meaningful integration of technology. It details a six-stage lesson plan (motivation, exploration, conjecture, explanation/proof, practice, reflection) designed to address common student errors and promote deeper conceptual understanding. The framework also incorporates assessment strategies, including rubrics and e-portfolios, to measure the development of spatial reasoning and problem-solving competencies. This research aims to provide educators with a practical, evidence-based methodology to transform traditional geometry instruction into a dynamic, interactive, and effective learning experience.
Keywords: Geometry Education, Visual Tools, TPACK, Dynamic Geometry Software, Spatial Reasoning, Augmented Reality, Assessment Rubrics.